Psychosocial supportive care services for haematopoietic stem cell transplant patients; a service evaluation of three UK transplant centres. (11th December 2013) - Horne, B.; Gilleece, M.; Jackson, G.; Snowden, J.A.; Liebersbach, S.; Velikova, G.; Wright, P.
<x xml:space="preserve">Abstract</x> Following haematopoietic stem cell transplant (HSCT) some patients experience long‐term physical and psychosocial problems which impact on everyday life. The aim of this service evaluation was to investigate the psychosocial supportive care available for HSCT patients in three UK centres, particularly related to five identified areas of concern: fatigue; psychological distress; vocational and financial issues; sexuality, and fertility. HSCT health professionals were invited to audio‐recorded semi‐structured interviews. Enquiry was made into supportive care provided routinely (proactive), provided in response to a need (reactive) and missing (gaps in service) from pre‐transplant to 18 months post transplant. Information gathered was transcribed and subjected to framework analysis. Interviews were conducted with 84 staff including nurses, doctors, psychologists, social workers, physiotherapists, dieticians and occupational therapists. Support for the five main areas of concern was variable across centres particularly with limitation of services for psychology; sexual dysfunction and fertility. Pro‐active interventions such as psychological screening were rare with support being more commonly provided in response to an identified need. Support provided reactively for the areas of concern was comprehensive across professional groups and centres. Further work explores patients' psychosocial issues and other ways of providing adjuvant support.